Upaya Meningkatkan Prestasi Belajar Siswa Melalui Model Pembelajaran Talking Stick di SMPN 1 Takeran Tahun Ajaran 2023-2024 - Anis Purwati; Sanusi Sanusi; Sri Handayani (Departement of Mathematics Education, 2024)
This research is based on the low learning achievement and motivation to learn mathematics in class VIII A students at SMP Negeri 1 Takeran Magetan. Therefore, this research was conducted with the aim of finding out whether the application of the talking stick type cooperative learning model can improve the achievement and learning motivation of class VIII A students at SMP Negeri 1 Takeran Magetan. The focus of this research itself is on student achievement and learning motivation in mathematics subjects involving triangles and quadrilaterals using the talking stick type cooperative learning model. This research was carried out with one initial observation and 2 cycles. From the results of this research, it was found that in the initial observation process of the learning process, teacher activities showed insufficient qualifications (K), activities and student evaluation test results showed insufficient qualifications (K). In cycle I of the learning process, teacher activities showed good qualifications (B), activities and student evaluation test results showed sufficient qualifications (C). Meanwhile, in Cycle II, the student learning process and achievement increased with good qualifications (B) seen from student activities and also student learning outcomes during the learning process. Therefore, it can be concluded that by implementing the talking stick type cooperative learning model, it can improve students' mathematics learning achievement at SMP Negeri 1 Takeran Magetan.